An Economic Order Quantity Model with Completely Backordering and Nondecreasing Demand under Two-Level Trade Credit. (30th December 2014) - Molamohamadi, Zohreh; Arshizadeh, Rahman; Ismail, Napsiah; Azizi, Amir
Abstract : In the traditional inventory system, it was implicitly assumed that the buyer pays to the seller as soon as he receives the items. In today's competitive industry, however, the seller usually offers the buyer a delay period to settle the account of the goods. Not only the seller but also the buyer may apply trade credit as a strategic tool to stimulate his customers' demands. This paper investigates the effects of the latter policy, two-level trade credit, on a retailer's optimal ordering decisions within the economic order quantity framework and allowable shortages. Unlike most of the previous studies, the demand function of the customers is considered to increase with time. The objective of the retailer's inventory model is to maximize the profit. The replenishment decisions optimally are obtained using genetic algorithm. Two special cases of the proposed model are discussed and the impacts of parameters on the decision variables are finally investigated. Numerical examples demonstrate the profitability of the developed two-level supply chain with backorder.